Virtual Tour Berbasis 3D Perumahan Griya Antasari Permai Bandar Lampung - Kurniawan, Rio; Agus, Isnandar; Rahman, Imron (TEKNIKA, 2022)
Griya Antasari Permai Housing is a housing complex located in Bandar Lampung. Marketing of Griya Antasari Permai Housing is done by distributing catalogs and brochures. Media brochures that are used today only display houses in the form of photos to give a picture to prospective buyers, so they cannot see the shape of the house offered from various angles. 3-dimensional (3D) visualization techniques can be used to add value in marketing housing. The technique used in the form of a Virtual Tour with the concept of Walk-Through is to make the user can see the visualization of the shape of the housing and its surroundings from various angles in more detail. 3D housing objects are created using GoogleSketchUp Software. This application system is designed using the Multimedia Development Life Cycle (MDLC) method. Virtual Tour application helps consumers know the detailed form of Griya Antasari Permai Housing from various angles. This application can only be operated on the Android operating system and it is hoped that this application developer can see the construction of residential buildings using animation and adding characters that can move so that it looks more real.